Paul, Christian textuality and the hermeneutics of Late Antiquity essays in honor of Margaret M. Mitchell - Moessner, David P. 1949-; Duff, Paul B. 1952-; Spittler, Janet E. 1976-; Calhoun, Robert Matthew 1971-; Mitchell, Margaret Mary 1956- (Leiden Boston Brill, 2023)
The essays in the present volume celebrate the work of Margarat M. Mitchell (University of Chicago) by engaging, extending, and challenging her ground-breaking research in three areas: (1) the letters of Paul the Apostle, both authentic and pseudoepigraphic; (2) the emergence and rapid development of early Christian literary culture over the first few centuries of the cult's existence; and (3) Late Antique interpretive practices and perspectives, particularly amoung patristic readers of the scriptures
Includes bibliographical references and indexes
Archivierung/Langzeitarchivierung gewährleistet
Keywords: Paul -- the Apostle, Saint; Bible -- History; Festschrift; Aufsatzsammlung